Suppression of leukocyte chemotaxis by human IgA myeloma components (The Rockefeller University Press, 1976)
Sera from patients with IgA myeloma suppressed polymorphonuclear leukocyte (PMN) chemotaxis, while generally little or no suppression was observed with sera from patients with IgG myeloma or Waldenstrom's macroglobulinemia. Chemotactic inhibitory activity was not limited to a single chemotactic factor and was equivalent when C5a, bacterial factor, casein, or normal serum were used as chemotactic attractants. No association was noted between the degree of inhibitory activity and the IgA subclass or light chain type. Chemotactic inhibitory activity was found to be directly associated with isolated IgA M components, and similar chemotactic suppression was noted with purified preparations of normal human colostral IgA. By comparison, IgA preparations were most effective in suppressing PMN chemotaxis and had a much lesser effect on monocyte chemotaxis. The mode of IgA chemotactic inhibition was cellular and at least partially reversible after a 37degreesC incubation in the absence of IgA. Some inhibition of PMN random mobility was noted with certain IgA preparations, although such effects did not parallel the degree of chemotactic inhibition. Fractionation of IgA myeloma sera and IgA M components by sucrose density gradient centrifugation showed multiple peaks of inhibitory activity in 10 to 13S fractions. The majority of IgA inhibitory activity was lost after pepsin digestion or sulfhydryl reduction and alkylation of isolated M components. When isolated IgA M components were fractionated on Sephadex G-200, inhibitory activity was associated with the exclusion volume and was abolished by reduction and alkylation procedures which resulted in a conversion of polymeric IgA to monomeric IgA.